Philosophy of Education in the 21st Century: Critical Thinking and the Role of the Teacher - Baltodano Goulding, Rafael (2025)
There is a direct correlation between the philosophy of education at different time periods and the prevailing social needs. Nowadays, the acquisition of knowledge or access to information is readily available, and the difficulty lies more in the ability to filter and process a sizable amount of information. For this reason, critical reasoning becomes particularly important. Critical reasoning involves developing reading skills, logical reasoning, and argumentation. The process of critical reasoning is not complete until the individual’s ideas are subject to peer review. Argumentation as a cognitive process faces three fundamental moments: conflict, collaborative reconstruction of thinking, and examination of theories and principles that support it. The professor within the current philosophy of education should be a motivator. Furthermore, they should facilitate the process of critical reasoning, not only aiding with the technical content of a particular area but also with the process of critical reasoning. The main goal of education greatly depends on the philosophical perspective followed and has changed over time. Considering society’s needs in this new century, it is essential to find a balance between shaping a happy and capable human being and addressing the specific needs of society.